(untitled) (The Peerian Journal, 2024)
The problem of climate change has become a threat to the entire world, and threatens the melting of ice blocks in many regions of the world. Therefore, an alga is an environmental solution to purify the air from gases emitted and harmful to the environment. The diverse development in employing algae to overcome environmental obstacles has stimulated ensuring sustainability. The word sustainability refers to comprehensive constructive improvements to the environment that include abundant dynamism and its systems. Rapid population growth and rapid civilization have led humanity to comprehensively exploit nature and its vibrant resources. However, today humans have realized the disasters they have caused due to their past mistakes and are already facing future challenges related to livelihood. Today, it has been shown that the discovery and development of eco-friendly, costeffective and cutting-edge strategies to address current sustainability shortcomings such as sustainable agriculture solutions, raw material crisis, pollution, carbon neutrality, industrial effluent and wastewater treatment, energy crisis have led to polluting the natural ecosystem. Advances in mycology research and allied fields have shown positive promise on the path to green transformation and maintaining sustainable environments. Algae can be an obvious factor to be employed in developmental activities, as it can replace various domestic needs and actions of humans. This review discusses the broad opportunities for using algae for basic sustainability